12x-12=3(2x+12)

Simple and best practice solution for 12x-12=3(2x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-12=3(2x+12) equation:


Simplifying
12x + -12 = 3(2x + 12)

Reorder the terms:
-12 + 12x = 3(2x + 12)

Reorder the terms:
-12 + 12x = 3(12 + 2x)
-12 + 12x = (12 * 3 + 2x * 3)
-12 + 12x = (36 + 6x)

Solving
-12 + 12x = 36 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-12 + 12x + -6x = 36 + 6x + -6x

Combine like terms: 12x + -6x = 6x
-12 + 6x = 36 + 6x + -6x

Combine like terms: 6x + -6x = 0
-12 + 6x = 36 + 0
-12 + 6x = 36

Add '12' to each side of the equation.
-12 + 12 + 6x = 36 + 12

Combine like terms: -12 + 12 = 0
0 + 6x = 36 + 12
6x = 36 + 12

Combine like terms: 36 + 12 = 48
6x = 48

Divide each side by '6'.
x = 8

Simplifying
x = 8

See similar equations:

| X/7-2=x/7 | | x/2+3=9 | | a/4-2=3 | | 0.45x+.05(14-x)=.10(63) | | 4(2+q)=-18 | | 2x-450=89x | | -1/2+3p=1.2 | | 5(2x+3)=10x-10 | | 4n-4=12 | | 7+6=113 | | 4x^2+37x-30=0 | | 5x-8=2x+8 | | v=1/3(3.14^2)h | | -1/2+3=-9 | | y=2x^2-2x | | 21a+16a= | | -1/2+3=-7 | | 11=47y | | 3(x+4)+6(x+2)= | | 4x-3-2x=17 | | 162/3-43/4 | | 3x-1-2x=11 | | 6x+4-4x=20 | | 10x+5=13x-10 | | 5x+1-3x=17 | | f(x)=2x^2-5 | | y+2y=3z | | X+3+x=21 | | 170=(3x+2)2x | | 4x+7+x=27 | | 2x+1+2x=13 | | 36-x=72 |

Equations solver categories